Cost and Reimbursement of Providing Routine Vaccines in Outpatient Obstetrician/Gynecologist Settings. Issue 1 (January 2021) - Dempsey, Amanda F.; Pyrzanowski, Jennifer; Campbell, Jonathan; Brewer, Sarah; Sevick, Carter; O'Leary, Sean T.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;223:562.e1–562.e8) Both nationally and globally, immunization rates among adults are poor. Greater efforts are needed to improve vaccination rates.